DESAIN SISTEM INFORMASI AKUNTANSI KEUANGAN BERBASIS JARINGAN DENGAN ALLOCATION ACCESS LIST SEBAGAI UPAYA PENINGKATAN PELAYANAN KEUANGAN DI UNIVERSITAS MUHAMMADIYAH SURABAYA - Ghiyats Syafiq Abriyansyah (UMSurabaya Publishing, 2008)
In general, the management has the desire to survive and even more progress in carrying out its duties as a key element in an institution, so that required an effort and an intelligent and creative innovation by management for institutions that managed to survive and could be much better. The first thing to do is to further strengthen the performance of the institution itself, and one of them is through the development of financial accounting information system. Development of financial accounting information system will support the operational activities within the company both in its capacity as a service provider for students and for internal purposes or university institution itself. Financial accounting information system is good, will have an impact on over all lines in an optimal institution. Making it easier for management decision-making processes associated with development institutions and those objectives can be achieved.The purpose of this study was to find out how the Financial Accounting Information Systems Design to suit the needs of Muhammadiyah University of Surabaya-Based Networks With Access Allocation List For Improving Financial Services Muhammadiyah Universityof Surabaya.Problems faced by the University of Surabaya is about the design of financial accounting information system is applied, so the impact on less than optimal performance of applications used to perform data processing.As for alternative solutions to problems that can be done Muhammadiyah University of Surabaya is redesigning the system by way of application of financial accounting information system-based network with Access Allocation List in accordance with the proposal given by the researchers.Based on this research note that the data input process occurs repeatedly in several applications and journalizing process was done manually, causing the data processing becomes long. This causes the required information management can not be served immediately and the truth of the financial statements can not be guaranteed for accuracy. To so management can integrate all application systems that are used so that the information produced better quality, effective and efficient. Kata Kunci: Sistem Informasi Akuntansi Keuangan, Jaringan, Allocation Access List.